Pengukuran Intensitas dan Pemetaan Kebisingan di Area Fatty Acid Plant PT. XYZ - C Sirait, benni Pranatal; Sutrisno, Sutrisno; Hasibuan, Chalis Fajri (Universitas Medan Area, 2024)
PT. XYZ is a factory engaged in processing of palm oil derivatives in producing a fatty acid. The machines used in the processing process at PT. Permata Hijau Palm Oleo KIM II Mabar generate the noise. This research aimed to find out the existing noise level and noise mapping, also the proposal of noise control on the production floor. Then, the data collection method conducted through observation using the equivalent noise level (Leq) method and noise mapping was through surfer 14. The data collection conducted in 16 points on the production floor. Furthermore, the result and noise distribution pattern showed that the high noise level was in several points, those were point 5 (85.77); point 6 (86.82); point 7 (86.33), point 8 (88.18); point 10 (86.96); point 13 (86.85); point 14 (87.67). The allowed threshold value refers to the Decree of the Minister of Manpower and Transmigration No.Per.13/MEN/X/2011 is 85 dB. Thus, the company needs to perform noise control such as barrier usage, regularly and scheduled machine maintenance to prevent and decrease the effect of the noise.